Interesting Times: A Twentieth-Century Life - Mouat, Jeremy (Labour / Le Travail, 2003)
The article reviews the book, "Interesting Times: A Twentieth-Century Life," by Eric Hobsbawm.
Keywords: AUTOBIOGRAPHY; BOOKS – Reviews; HOBSBAWM; E. J. (Eric J.); 1917-2012; INTERESTING Times: A 20th Century Life (Book); Nonfiction